Solar vortex engine: Experimental modelling and evaluation - Al-Kayiem, H.H. (Elsevier Ltd, 2018)
This main objective of the present paper is to introduce a novel developed model of solar vortex engine (SVE). The system design, implementation, aero-thermo-dynamic measurements and analysis have been presented and discussed. The system consists of solar air collector, 8.0 m diameter and 8.8Â° inclined Perspex canopy, and vortex generation engine (VGE) has a cylindrical shape with an outer diameter of 1.0 m and 1.0 m height. Air was guided from the collector to the arena of vortex generation engine through eight air entry slots with guide vanes which impose the air stream to move in rotational manner. The results of this study demonstrated that the developed SVE was capable to produce swirly updraft flow with tangent to axial velocity ratio of 7.5 at the top exit plane of the VGE. At mean solar radiation of 1040 W/m2 and ambient temperature 35.6 Â°C, air temperature in the vortex region was about 48â49 Â°C. The proposed design of the SVE, introduced and experimented in this work, is sufficient to generate the updraft vortex flow. It is recommended to carry out numerical analysis to extend the investigation for the geometrical effects on the system performance. Â© 2018 Elsevier Ltd